Respuesta :
Step-by-step explanation:
1. y=2x-3 x=1 y=-1
-1=2x1 - 3
-1=2-3
-1=-1 (LHS=RHS) C.(1,-1)
2. y=-3x+4 x=2, y=-2
-2=-3x2 +4
-2=-6 +4
-2=-2 (LHS=RHS) D.(2,-2)
The ordered pair of the linear equations y = 2x - 3 and y = -3x + 4 are as follows:
1. (1, -1)
2. (2, -2)
Linear equation
- y = mx + b
where
m = slope
b = y-intercept
Therefore,
y = 2x - 3
The value of y is gotten when we substitute the value of x in the equation. Therefore,
y = 2(1) - 3
y = 2 - 3 = -1
Therefore, the ordered pair is (1, -1)
2.
y = -3x + 4
y = -3(2) + 4
y = -6 + 4
y = -2
Therefore, the ordered pair is (2, -2).
learn more on linear equation here: https://brainly.com/question/1983094